2002
DOI: 10.1002/1521-3951(200201)229:1<287::aid-pssb287>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Sites of Phosphorus in ZnMnTe - A Compensation Study

Abstract: In this paper we investigate phosphorus doped ZnMnTe by means of infrared absorption. We report pronounced changes in the absorption spectra upon increasing phosphorus doping and upon annealing at 850 C in nitrogen atmosphere at high pressure. From the far-infrared local vibrational spectra we identify the lattice sites of phosphorus in ZnMnTe and interpret the strong compensation of the as-grown material in terms of at least partial passivation by hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Since transport measurements [12,13] show that the p-type sample in question remains on the insulator side of the MIT, we begin the interpretation of our findings by evaluating the expected magnitude of the hole-induced energy shift if the holes were strongly localized at individual acceptor sites. From earlier studies of bound magnetic polarons in p-type DMSs [19], we know that the Mn spins residing at the distance r from the acceptor experience a molecular field,…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Since transport measurements [12,13] show that the p-type sample in question remains on the insulator side of the MIT, we begin the interpretation of our findings by evaluating the expected magnitude of the hole-induced energy shift if the holes were strongly localized at individual acceptor sites. From earlier studies of bound magnetic polarons in p-type DMSs [19], we know that the Mn spins residing at the distance r from the acceptor experience a molecular field,…”
mentioning
confidence: 59%
“…However, it has been shown previously by some of us that large single crystals of Zn 1ÿx Mn x Te:P can be prepared [13], in which Mn and hole concentrations are sufficiently high to observe ferromagnetic ordering. Our Zn 1ÿx Mn x Te crystals are grown by the high pressure Bridgman method from ZnTe 1ÿx MnTe x solution in an evacuated (10 ÿ6 Torr) quartz ampoule, with phosphorus corresponding to the doping level of 5 10 19 cm ÿ3 added in the form of Zn 3 P 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the degeneracy at the N Se (P Se ) site is lifted due to Mn alloying, the ATM-GF calculation [50] for Mn Zn - 14 N Se (Mn Zn -P Se ) pairs ascribed two modes (see Table 4), one A 1 appearing at a lower frequency and the other E at a higher frequency of the main 14 N Se (P Se ) F 2 local mode. In the absence of experimental results for p-doped Zn 1−x Mn x Se, our simulations offered compelling validations to impurity modes by IR spectroscopy [64] of low phosphorous dopant levels in dilute Zn 1−x Mn x Te ( x  < 0.025).…”
Section: Numerical Calculations Results and Discussionmentioning
confidence: 83%
“…Specifically, it has been recently found that annealing under high pressure of nitrogen gas of Bridgman-grown crystals of Zn 1-x Mn x Te doped with phosphorus (P) allows one to obtain hole concentrations as high as 5×10 18 cm -3 at T=300 K for x=0.05 [2]. Specifically, it has been recently found that annealing under high pressure of nitrogen gas of Bridgman-grown crystals of Zn 1-x Mn x Te doped with phosphorus (P) allows one to obtain hole concentrations as high as 5×10 18 cm -3 at T=300 K for x=0.05 [2].…”
Section: Electrical Magnetic and Magnetooptical Properties Of Bulk (mentioning
confidence: 99%